2016
DOI: 10.3847/0004-637x/825/1/22
|View full text |Cite
|
Sign up to set email alerts
|

THE C–H STRETCHING FEATURES AT 3.2–3.5 μm OF POLYCYCLIC AROMATIC HYDROCARBONS WITH ALIPHATIC SIDEGROUPS

Abstract: The so-called "unidentified" infrared emission (UIE) features at 3. 3, 6.2, 7.7, 8.6, and 11.3 μm are ubiquitously seen in a wide variety of astrophysical regions. The UIE features are characteristic of the stretching and bending vibrations of aromatic hydrocarbon materials, e.g., polycyclic aromatic hydrocarbon (PAH) molecules. The 3.3 μm aromatic C-H stretching feature is often accompanied by a weaker feature at 3.4 μm. The latter is generally thought to result from the C-H stretch of aliphatic groups attac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…But Yang et al (2016) have shown that the aliphatic fraction of the UIE carriers derived from the A3.4/A3.3 ratios of PAHs with a wide range of sidegroups (e.g., ethyl, propyl, butyl, dimethyl) was close to that based on the A3.4/A3.3 ratios of mono-methyl PAHs. Also, the sample of regular and methylated PAHs considered here (see Figure 1) may not be representative of what are actually present in astronomical environments (e.g., the actual astro-PAH molecules may have NC > ∼ 40 C atoms [Tielens 2008] while the largest molecule considered here is coronene of NC = 24).…”
Section: Discussionmentioning
confidence: 89%
“…But Yang et al (2016) have shown that the aliphatic fraction of the UIE carriers derived from the A3.4/A3.3 ratios of PAHs with a wide range of sidegroups (e.g., ethyl, propyl, butyl, dimethyl) was close to that based on the A3.4/A3.3 ratios of mono-methyl PAHs. Also, the sample of regular and methylated PAHs considered here (see Figure 1) may not be representative of what are actually present in astronomical environments (e.g., the actual astro-PAH molecules may have NC > ∼ 40 C atoms [Tielens 2008] while the largest molecule considered here is coronene of NC = 24).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, we obtain for PAH cations A 3.3 ≈ 0.92 km mol −1 , A 3.4 ≈ 3.20 km mol −1 , and A 3.4 / A 3.3 ≈ 3.48. We note that, although these results were derived from the mono-methyl derivatives of small PAH molecules, it has been shown in Yang et al (2016b) that the A 3.4 /A 3.3 ratios determined from the PAH molecules attached with a wide range of sidegroups (including ethyl, propyl, and butyl) as well as dimethyl-substituted pyrene are close to that of mono-methyl PAHs.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Its 8.6 and 11.3 µm PAH features are spatially extended on a few 100 AU scale , and the spatial distribution of the 3.3 µm emission shows a gap in the innermost region (R ∼ 5-10 AU) and is extended up to ∼ 50 AU (Habart et al 2006) or R ∼ 12 ± 3 AU (Geers et al 2007b). Minor features at 3.4 and 3.46 µm are also detected (Habart et al 2006), which could be attributed to aliphatic C-H stretches in methyl or ethyl side-groups attached to PAHs (e.g., Joblin et al 1996;Yang et al 2013Yang et al , 2016b. Lisse et al (2007) compared the MIR spectrum (5-35 µm) of HD 100546 with those of Comet 9P/Tempel 1 and Comet C/ 1995 O1 (HaleBopp), which shows similar emission signatures including PAH features as well as crystalline silicate features.…”
Section: A25 Hd 100546mentioning
confidence: 99%
“…They are usually attributed to the C-H vibrational modes in aliphatic hydrocarbons (e.g., Chiar et al 2000;Pendleton & Allamandola 2002;Yang et al 2016aYang et al , 2016b although the 3.43 µm feature can also originate from anharmonicity and/or superhydrogenation of the aromatic C-H stretch (Barker et al 1987;Bernstein et al 1996). Among the 63 MIR spectra that have the spectral data at λ 6.9 µm, 21 sources show the aliphatic feature at 6.9 µm, which is indicative of aliphatic CH sidegroups of PAH molecules in those systems.…”
Section: Aliphatics Versus Aromaticsmentioning
confidence: 99%